Evaluation and assessment of the effectiveness of the DSWD internal and external convergence as operationalized by the regional, provincial, and city/municipality action teams - Jose Ramon G. Albert; Connie B. Dacuycuy (Philippine Institute for Development Studies (PIDS), 2017)
This study aims to describe and examine organizational structures, business processes, and capacity development, as they relate to the design of the Department of Social Welfare and Development's (DSWD) Convergence Strategy. The process evaluation is useful from an organizational learning perspective since DSWD wants to improve the quality of its work. This process evaluation employed a mixed-methods approach which integrates qualitative and quantitative analysis. Key findings on organizational structures underscore the need to take stock of DSWD documents and update them; key findings on business processes emphasize the need to strengthen information technology initiatives for internal and external use; and key findings on capacity development include the need to define specific deliverables on internal and external convergence at all levels. There is also a need to strengthen feedback channels and data sharing for enhancing strategic external partnerships.
Keywords: 330; Convergence Strategy; social protection; process evaluation; organizational structures; business processes; capacity and partnership development